Предмет: Алгебра, автор: assema1998

26 БАЛЛОВ!!!СРОЧНО!!!
вычислите
( sqrt[6]{5+2 sqrt{6} }+ sqrt[3]{ sqrt{3}+ sqrt{2}  }  )* sqrt[3]{ sqrt{2}- sqrt{3}  }

Ответы

Автор ответа: sukonnikoffma
0
5+2 sqrt{6} =5+2 sqrt{2}  sqrt{3} =2+2 sqrt{2}  sqrt{3} +3= (sqrt{2})^2+ 2 sqrt{2}  sqrt{3} +( sqrt{3} )^2=
\ = ( sqrt{2}+ sqrt{3} )^2
\  sqrt[6]{5+2 sqrt{6}}= sqrt[6]{ ( sqrt{2}+ sqrt{3} )^2} =  sqrt[3]{ sqrt{2}+ sqrt{3}  } 
\ (sqrt[3]{ sqrt{2}+ sqrt{3}  } +  sqrt[3]{ sqrt{3} + sqrt{2} } )* sqrt[3]{ sqrt{2} - sqrt{3} } 
\ 2*sqrt[3]{ sqrt{2}+ sqrt{3}  }*sqrt[3]{ sqrt{2} - sqrt{3} } =2 sqrt[3]{( sqrt{2}+ sqrt{3})*( sqrt{2} - sqrt{3} )  } =
\ = 2* sqrt[3]{2-3} =2*(-1)=-2
Похожие вопросы
Предмет: Литература, автор: stasuan14